FINANCIAL PERFORMANCE AND ITS DETERMINANTS: A CASE STUDY OF FISH DRYING BUSINESS IN SUMBER JAYA VILLAGE, KAMPUNG MELAYU DISTRICT, BENGKULU CITY - Sriyoto Sriyoto; Ketut Sukiyono; Cesa Sri Wulandari (BPFP Faperta UNIB, 2020)
This study aims to analyze the level of financial performance and the factors that influence it in the bussines of fish drying in Sumber Jaya Village, Kampung Melayu District, Bengkulu City as measured by the level of profit and R / C Ratio. Respondents in this study are 120 partisans working on fish drying . Data analysis methods are profit analysis, R / C Ratio, and Multiple Linear Regression in the form of Double-Log using Shazam tools. The results showed that the average profit in one processing is Rp 529,185, while the average R / C Ratio in one production process is 2, which showed that the bussines of fish drying in Sumber Jaya Village is feasible . However, partially, the variables of age and business scale are significantly determine tothe profit rate of the bussines of dried fish processing, in addition, the only business scale variables and entrepreneur characteristics are that partially significantly determine the level of efficiency of the bussines of dried fish processing